Corpus et alternance codique : que peut nous apprendre une approche comparative ? - Charles Brasart (Corela)
This article aims at demonstrating that corpus-based research is the methodology that is most apt at correctly describing the phenomena involved in code-switching. By putting the individual speakers and their interactions as a group at the center of the stage, it makes it possible to analyze code-switching as a speech-based phenomenon arising from interpersonal exchanges, rather than from a hypothetical ideal speaker. Basing my claims on the comparative analysis of two bilingual corpora, I will show that this methodology enables the linguist to isolate tendencies that seem valid independently of the groups under scrutiny, as well as phenomena that only appear in one group or the other. I conclude that research on code-switching, if it is to avoid mistaking idiosyncrasies for universals, should be carried out using corpus analyzes and systematic comparisons between corpora.